The Impact of Problem-Based Learning on The Biology Achievement of Grade XI Students at SMAN 1 Sikur, East Lombok - M. Alhafizin; Supratman Supratman; Mirzan Asri; Intan Lestari Shelvyandira (Indonesian Journal of Educational Innovation, 2025)
The increasing demand for 21st-century education requires innovative learning models that enhance students’ critical thinking and problem-solving skills. This study aims to analyse the effect of the Problem-Based Learning (PBL) model on Biology learning outcomes among Grade XI students at SMAN 1 Sikur, East Lombok. A quantitative approach was employed using a quasiexperimental design with a pretest–posttest control group. The sample consisted of two classes, XI IPA 1 (control group) and XI IPA 3 (experimental group), each comprising 30 students. Data were collected through pretests and post-tests and analysed using an independent samples t-test. The results showed a significant difference in post-test scores between the experimental group (81.2) and the control group (73.3), with a p-value of 0.0006 (p < 0.05). It can be concluded that the PBL model has a significant positive impact on students’ biology learning outcomes. These findings imply that PBL can be a practical instructional approach to foster meaningful and skilloriented learning in secondary education.